Spinal Cord Infarction in the Region of the Posterior Spinal Artery After Embolization for Vertebral Artery Dissection. Issue 6 (9th March 2018) - Tsuruta, Wataro; Yamamoto, Tetsuya; Ikeda, Go; Sato, Masayuki; Ito, Yoshiro; Takigawa, Tomoji; Marushima, Aiki; Nakai, Yasunobu; Matsumaru, Yuji; Matsumura, Akira
Abstract: BACKGROUND: Endovascular surgery for vertebral artery dissections (VADs) carries the risk of spinal cord infarction (SCI). Although SCI in the region of the anterior spinal artery (ASA) has been reported, SCI in the region of the posterior spinal artery (PSA) is rare. OBJECTIVE: To investigate PSA infarction after endovascular surgery for VAD. METHODS: Infarction in the region of the PSA after endovascular surgery for VADs carried out in consecutive 21 cases was investigated. The variables of aneurysmal location, status, intra-aneurysmal thrombosis, antithrombotic therapy, and endovascular procedure were investigated in relation to the occurrence of spinal cord or brain stem infarction. RESULTS: Thirteen cases were unruptured aneurysms, and 8, ruptured aneurysms. The endovascular surgical method was internal trapping in 10 cases, stent-assisted coil embolization in 8 cases, and proximal occlusion (PO) in 3 cases. Periprocedural symptomatic infarction was detected in 4 of the 21 cases (19%): 3 SCIs and 1 lower medulla infarction, after 1 stent-assisted coil embolization and 3 PO. All 3 symptomatic SCIs were PSA infarction. On univariate analysis, the variables of posterior inferior cerebellar artery-involved-type, PO, and intraprocedural proximal flow arrest were significantly correlated with occurrence of PSA infarction. CONCLUSION: PSA infarction after endovascular surgery for VAD seems not to be a rare potential complication. Insufficiency of collateral blood flow and artery-to-artery embolism due to intraprocedural flow stagnation of the VA seem to be the possible mechanisms of PSA infarction in addition to previously reported mechanisms such as direct obliteration by the embolic materials and extended thrombosis of the VA stump.